HUBUNGAN ANEMIA DAN PARITAS DENGAN KEJADIAN PERDARAHAN POST PARTUM PADA IBU BERSALIN DI RUMAH SAKIT MUHAMMADIYAH PALEMBANG TAHUN 2012 - Indah Rahmadaniah (Jurnal Kesehatan Abdurrahman, 2012)
Blood of Post Partum is blood more than 500-600 ml during 24 first hour after child born. Factors cause of blood of post partum that was Anaemia, uteri antonia, placenta retensio , rest of placenta, born and parity. In order to be known anaemia relation and parity with occurence of blood of post partum at mother’s pregnant At Home Muhammadiyah Hospital Palembang in 2012. The research represented research of analytic survey with approach of sectional cross. Population in this research was all mother’s pregnant At Muhammadiyah Hospital Palembang in 2012, with sample that was counted 56 taken responder with sampling acedental. Data processed analysed bivariate and univariat. From result of done research at 56 responder in earning from result of bivariate analysis by using test of statistic that was test of chi square at correction continuity found that p value 0,03 =0,05 meaning there was relation having a meaning among anemia with occurence of blood of post partum at mother’s pregnant. While for parity from result of test of statistic that was test of chi square at correction continuity found that p value 0,01 =0,05 meaning there was relation having a meaning among parity with occurence of blood of post partum at mother’s pregnant. According to this research in expecting midwife improve more optimal role and service through training - research so that midwife can execute role better.